Mouse Behavioral Assays Relevant to the Symptoms of Autism - Crawley, Jacqueline N. (Blackwell Publishing Ltd, 2007)

(untitled) (Brain Pathol)
While the cause of autism remains unknown, the high concordance between monozygotic twins supports a strong genetic component. The importance of genetic factors in autism encourages the development of mutant mouse models, to advance our understanding of biological mechanisms underlying autistic behaviors. Mouse models of human neuropsychiatric diseases are designed to optimize (i) face validity (resemblance to the human symptoms) (ii) construct validity (similarity to the underlying causes of the disease) and (iii) predictive validity (expected responses to treatments that are effective in the human disease). There is a growing need for mouse behavioral tasks with all three types of validity, to define robust phenotypes in mouse models of autism. Ideal mouse models will incorporate analogies to the three diagnostic symptoms of autism: abnormal social interactions, deficits in communication and high levels of repetitive behaviors. Social approach is tested in an automated three chambered apparatus that offers the subject a choice between spending time with another mouse, with a novel object, or remaining in an empty familiar environment. Reciprocal social interaction is scored from videotapes of interactions between pairs of unfamiliar mice. Communication is evaluated by measuring emission and responses to vocalizations and olfactory cues. Repetitive behaviors are scored for measures of grooming, jumping, or stereotyped sniffing of one location or object. Insistence on sameness is modeled by scoring a change in habit, for example, reversal of the spatial location of a reinforcer in the Morris water maze or T‐maze. Associated features of autism, for example, mouse phenotypes relevant to anxiety, seizures, sleep disturbances and sensory hypersensitivity, may be useful to include in a mouse model that meets some of the core diagnostic criteria. Applications of these assays include (i) behavioral phenotyping of transgenic and knockout mice with mutations in genes relevant to autism; (ii) characterization of inbred strains of mice; (iii) evaluation of environmental toxins; (iv) comparison of behavioral phenotypes with genetic factors, such as unusual expression patterns of genes or unusual single nucleotide polymorphisms; and (v) evaluation of proposed therapeutics for the treatment of autism.